Modes of Action of a Bi-domain Plant Defensin MtDef5 Against a Bacterial Pathogen Xanthomonas campestris - Velivelli, Siva L. S.; Islam, Kazi T.; Hobson, Eric; Shah, Dilip M. (Frontiers in Microbiology, 2018)
Defensins are small cysteine-rich endogenous host defense peptides expressed in all higher plants. They are thought to be important players in the defense arsenal of plants against fungal and oomycete pathogens. However, little is known regarding the antibacterial activity of these peptides. The genome of the model legume Medicago truncatula contains 63 genes each encoding a defensin with a tetradisulfide array. A unique bi-domain defensin, designated MtDef5, was recently characterized for its potent broad-spectrum antifungal activity. This 107-amino acid defensin contains two domains, 50 amino acids each, linked by a short peptide APKKVEP. Here, we characterize antibacterial activity of this defensin and its two domains, MtDef5A and MtDef5B, against two economically important plant bacterial pathogens, Gram-negative Xanthomonas campestris and Gram-positive Clavibacter michiganensis. MtDef5 inhibits the growth of X. campestris, but not C. michiganensis, at micromolar concentrations. MtDef5B, but not MtDef5A, exhibits more potent antibacterial activity than its parent MtDef5. MtDef5 and each of its two domains induce distinct morphological changes and cell death in X. campestris. They permeabilize the bacterial plasma membrane and translocate across membranes to the cytoplasm. They bind to negatively charged DNA indicating these peptides may kill bacterial cells by inhibiting DNA synthesis and/or transcription. The cationic amino acids present in the two γ-core motifs of MtDef5 that were previously shown to be important for its antifungal activity are also important for its antibacterial activity. MtDef5 and its more potent single domain MtDef5B have the potential to be deployed as antibacterial agents for control of a Xanthomonas wilt disease in transgenic crops.